Web based management system for blood bank, jaffna teaching hospital - Amidhayan, A. (University of Jaffna, 2018)
Jaffna teaching hospital is the main hospital in the Jaffna peninsula which is functioning with all the essential services. At present, it consists blood bank facility with manual based system. They are facing many difficulties in handling this service with the manual based system such as keeping the records of blood donors, documentation, retrieving information about blood donors. The “Web based Management System for blood bank, Jaffna” is to provide blood donors to view their blood donating history, get boost ups from the system, take part in the free health guidance forums conducted by a physician. With the help of this online system “Donors” can able to maintain their relationship with blood bank through this online system and they will be able to know about their blood donation history and also blood donation camp details.New donors can register with this system and login with their registered user Name & Password. Also donors can search for their medical history, get to know the needed blood group at the particular time. Blood bank administration can manage their records and make, customize reports. The system is developed according to the Object Oriented Architecture. Unified Modeling Language (UML) is also used in the Analysis & Design stages. The system is fully developed using Open Source Tools. Hypertext Pre-processor (PHP) & MySQL are used to build the system. Hyper Text Markup Language (HTML), Cascading Style Sheet (CSS), JavaScript also used for designing part and validation part.
Keywords: PHP; MYSLQ; Web development; Object oriented architecture